Strategic uncertainty in financial markets: Evidence from a consensus pricing service - Lerby M. Ergun; Andreas Uthemann (Bank of Canada, 2020)
This paper measures valuation and strategic uncertainty in an over-the-counter market. The analysis uses a novel data set of price estimates that major financial institutions provide to a consensus pricing service. We model these institutions as Bayesian agents that learn from consensus prices about market conditions. Our uncertainty measures are derived from their beliefs through a structural estimation. The main contribution of the consensus pricing service is to reduce strategic uncertainty in the most opaque market segments. This stresses the importance of public data, such as financial benchmarks, for a shared understanding of market conditions in markets with limited price transparency.
Keywords: C58; D53; D83; G12; G14; 330; Financial institutions; Financial markets; Market structure and pricing